Roles of Oral Bacteria in Cardiovascular Diseases - From Molecular Mechanisms to Clinical Cases: Involvement of Porphyromonas gingivalis in the Development of Human Aortic Aneurysm - Koichiro Wada; Yoshinori Kamisaki (Elsevier, 2010)
Accumulating evidence suggests the involvement of Porphyromonas gingivalis (P. gingivalis), a periodontal pathogen, in cardiovascular diseases. Clinical specimens of aneurysmal tissue and dental plaque collected from patients infected with or without P. gingivalis were analyzed. The number of aneurysms in the distal aorta in the P. gingivalis -infected group was significantly higher than that in the non-infected group. Cellular accumulation of adipocytes in aneurysms was less frequently identified in the infected group. The expression of embryonic myosin heavy chain isoform, a phenotypic marker for proliferative smooth muscle cells, was higher in the P. gingivalis -infected group than the non-infected group. Clinical and histopathological features of aortic aneurysms associated with P. gingivalis infection are different from those present in non-infected patients. The major characteristic of P. gingivalis infection associated with aneurysms is smooth muscle cell proliferation in the distal aorta. Keywords:: Porphyromonas gingivalis (P. gingivalis), aortic aneurysm, smooth muscle cell, embryonic myosin heavy chain isoform, atherosclerosis, oral bacteria